Health Problems in Female Reproductive Organs - Linda Ayu Setya Indra S; Laura Morani Tamba; Nesti Taileleu; Yeti Mareta Undaryati (Journal of Global Research in Public Health, 2024)
Women's reproductive health is an important aspect of general health that involves complex organ systems and is susceptible to various disorders. The purpose of this article is to review health problems related to female reproductive organs. By providing comprehensive information on the impact and prevention of these health problems, it is hoped that public awareness of the importance of reproductive health services will increase. Health problems of female reproductive organs such as sexually transmitted infections, non-sexual infections, menstrual disorders, and hormonal disorders. Health problems in the female reproductive system can have a significant impact on quality of life and fertility. If left untreated, these health issues not only impact physical health, but also impact a woman's mental and emotional health, leading to stress related to fertility and overall health. Prevention of sexually transmitted infections (STIs) in women can be done through several effective strategies, including consistent condom use, vaccination against viruses such as Human Papillomavirus (HPV) and Hepatitis B can reduce the risk of infection, comprehensive sexual education, and open communication with partners regarding sexual health history. Women's reproductive health is a vital aspect that affects physical, mental, and social well-being. can experience various health problems. Women's reproductive health problems have an impact. These problems can be prevented to help maintain reproductive health and improve a woman's overall quality of life.